Power Electronic Transformer Using DC-DC Converter Based on Energy Injection Control - ZHAO Ziyi; SU Mei; ZHU Qi; WANG Hui (Kongzhi Yu Xinxi Jishu)
In order to improve the power density and efficiency of power electronic transformer, this paper presented a power electronic transformer using DC-DC converter based on energy injection control. It is based on the Buck converter, using a symmetrical topology and working in the energy injection mode. In this paper, working modes and working principle of both energy injection and free oscillation were analyzed in detail. Simulation results were presented to demonstrate the DC-DC converter always works in resonant softswitching state and maintains constant output current under dynamic load. It also verified that this novel power electronic transformer can achieve bidirectional power transfer and improve the efficiency.